Domestic work in France and Italy: comparative case studies on the contemporary diffusion of informal employment. (1st April 2012) - ,
Abstract : The persistence of informal employment and its recent development in Western countries is often disregarded. This article argues that a gendered renewal of informal employment is taking place following global economic restructuring. Furthermore, it shows how informality might be recreated through the very policy initiatives that aimed at combating informality and structuring the highly feminised sector of care and domestic services. In spite of the differences in policy initiatives, qualitative analysis illustrates how the formalisation of these jobs remains partial, in France as in Italy, regardless of the absence or the presence of specific politics of regularisation. Industrial unemployment due to rural deindustrialisation is imposing on working-class women — formerly largely employed in factories — a new form of domesticity through a certain recognition of domestic and care work, between formality, 'grey work' and informality, which confines these same women to a universe that is family-based and precarious.